AOPs Are Not Additive: On the Biogeo-Optical Modeling of the Diffuse Attenuation Coefficient - Lee, Zhongping; Shang, Shaoling; Stavn, Robert (Frontiers in Marine Science, 2018)
Commonly we see the diffuse attenuation coefficient of downwelling irradiance (Kd) expressed as a sum of the contributions of various constituents. We show here that, both theoretically and numerically, because Kd is an apparent optical property, this approach is not consistent with radiative transfer. We further advocate the application of models of Kd developed in past decades that are not only consistent with radiative transfer but also provide more accurate estimates, in particular for coastal turbid waters.